Pendidikan Islam Era Revolusi Industri 4.0 Esensi dan Urgensinya - Bahrudin, Bahrudin (Atthulab: Islamic Religion Teaching and Learning Journal, 2021)
The purpose of this study is to determine the essence and urgency of Islamic education in responding to the development of the Industrial Revolution Era 4.0. The data collection method in this research is literature study method. The way it works is that the researcher collects reading material that is relevant to the subject of the discussion. The concept of Islamic education includes: Definition, basics, objectives, functions, and the scope of Islamic education itself. The essence of Islamic education includes the following points: the essence of monotheism, the essence (worship, preaching, social), the essence of morals, the essence of history, the essence of science, the essence of tazkiyatunnafs, the essence of manners. Islamic education in the revolutionary era 4.0 occupies a very urgent and strategic position, this is in line with its goal, namely to direct students to become faithful and pious servants, always under divine guidance. Islamic education facilitates humans to learn and practice actualizing all their potential, both physical potential, aqliyah, and adabiyah. As the profile described by Allah Swt. in Q.S. 3: 190. Namely as a figure of ulil albab. Humans who are faithful, knowledgeable, and always productive in pious deeds in accordance with Islamic guidance. Â  Tujuan dari penelitian ini adalah untuk mengtahui esensi dan urgensi pendidikan Islam dalam menyikapi perkembangan Era Revolusi Industri 4.0. Metode pengumpulan data dalam penelitian ini adalah metode studi pustaka. Cara kerjanya adalah peneliti mengumpulkan bahan-bahan bacaan yang relevan dengan pokok pembahasan. Konsep Pendidikan Islam meliputi: Pengertian, Dasar-dasar, Tujuan, Fungsi, Ruang Lingkup pendidikan Islam itu sendiri. Esensi pendidikan Islam meliputi point: Esensi Tauhid, Esensi (Ibadah, dakwah, sosial), Esensi akhlak, Esensi Sejarah, Esensi Sains, Esensi Tazkiyatunnafs, Esensi sopan santun. Pendidikan Islam di era revolusi 4.0 ini menempati posisi yang sangat urgen dan strategis, hal ini selaras dengan tujuannya yaitu untuk mengarahkan peserta didik untuk menjadi hamba yang beriman dan bertaqwa, senantiasa dalam bimbingan Iilahi. Pendidikan Islam memfasilitasi manusia untuk belajar dan berlatih mengaktualisasikan segenap potensi yang dimilikinya, baik potensi jasmaniyah, aqliyah, serta adabiyah. Sebagaimana profilnya digambarkan oleh Allah Swt. dalam Q.S. 3:190. Yaitu sebagai sosok ulil albab. Manusia yang beriman, berilmu, dan selalu produktif dalam amal shaleh sesuai dengan tuntunan Islam.